The Trans-pacific strategic economic partnership agreement : a Latin American perspective - Herreros, Sebastian (UN ECLAC. Division of International Trade and Integration SantiagoCL)
Looks at the Trans-Pacific Strategic Economic Partnership Agreement (TPP or P4), with nine countries from Asia, Oceania and the Americas. Examines the short- to medium-term prospects of the TPP process and the possible implications for participating Latin American countries. Reviews some features of the current TPP members' economies. Describes the main elements of the agreement and examines how the current TPP process fits within the broader context of Asis Pacific regionalism. Reviews the main initiatives by Latin American countries to establish preferential trade links with Asia Pacific. Analyses the opportunities and risks that the TPP process poses to LA countries.